A Review on the Status of Genetic Characterization of Indigenous Goat Breeds in India - Shivahre, Pushp Raj; Dash, Soumya; Upadhyay, Arpan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The goat breeds are diverse and well-adapted to the local agroclimatic conditions in India. The indigenous and lesser-known populations, which make up 70% of the overall goat population and some of which are currently in danger of going extinct, have not yet had their genetic makeup fully determined. To maintain their genomic variability, which is necessary for genetic resource conservation and genetic resource improvement, genetic characterisation is required. For research on goat population structure and diversity, three genetic markers viz. microsatellites, mtDNA, and caprine SNP chips are used and their study has revealed that the most diversified breeds are Kanni Adu and Sirohi, whereas Osmanabadi is the least diverse breed. The genetic gap between Kanni Adu and Zalawadi was determined to be the greatest (0.519) and the genetic gap between Jamunapari and Marwari was the lowest (0.092). In Indian goats, phylogenetic and network research identified four widely recognised haplogroups (A, B, C, and D). Multiple maternal origins were identified in Chinese domestic goats, according to an origin and genetic diversity analysis based on mtDNA research. In addition to providing genetic divergence parameters, the information derived from caprine SNPChips also identifies selection signatures linked to a variety of useful qualities that contribute to a breed's uniqueness. Therefore, this review advises the registration and characterisation of local goat population to make a mission towards zero non-descript goat genetic resources in India by applying genomic technology.